Determine the expression for the flipped unit circle equation
Answer 1
To determine the equation for a unit circle flipped over the y-axis, we start with the standard unit circle equation:
$x^2 + y^2 = 1$
When we flip the unit circle over the y-axis, we change the sign of the x-coordinate. Therefore, the new equation becomes:
$(-x)^2 + y^2 = 1$
Simplifying this, we get:
$x^2 + y^2 = 1$
Thus, the equation of the unit circle flipped over the y-axis is the same as the original unit circle.
Answer 2
Starting with the unit circle equation:
$x^2 + y^2 = 1$
Flipping the unit circle over the y-axis involves changing the sign of the x-coordinate, resulting in:
$(-x)^2 + y^2 = 1$
Since $(-x)^2$ is the same as $x^2$, we simplify to get:
$x^2 + y^2 = 1$
Thus, the flipped unit circle over the y-axis retains the equation:
$x^2 + y^2 = 1$
Answer 3
The unit circle equation is:
$x^2 + y^2 = 1$
When flipped over the y-axis:
$(-x)^2 + y^2 = 1$
Simplifying:
$x^2 + y^2 = 1$
Start Using PopAi Today